PERAN LEMBAGA SWADAYA MASYARAKAT DALAM PENYELESAIAN HAK ASUH ANAK PASCA PERCERAIAN DI BANDA ACEH - Faizah Faizah; Rizkal Rizkal; Mansari Mansari; Zahrul Fatahillah (STIS Nahdlatul Ulama Aceh, 2021)
This study seeks to discuss the role of women's non-governmental organizations (NGOs) in resolving post-divorce custody of children. This is because the problem of post-divorce custody is always a struggle between father and mother. Sometimes custody is given to the mother in the decision of the Syar'iyah Court judge, but the empirical facts are taken by the father. This study aims to determine the roles, efforts and challenges faced by women's NGOs in resolving post-divorce custody of children. This type of research includes empirical juridical research. The primary legal materials used are Law Number 1 Year 1974, secondary legal materials and tertiary legal materials. Primary data obtained through interviews with respondents who carry out tasks in NGOs. Data analysis was carried out in a prescriptive manner which attempted to provide an explanation of primary data and secondary data and primary and secondary legal materials. The results showed that women's NGOs have a strategic role in resolving post-divorce custody issues, because most mothers resolve custody issues through women's NGOs. The efforts taken are: First, assisting them to the Police or Polres level to make a report to the Police. Second, assisting in reporting the case to P2TP2A. Third, bringing together the mother and father of the child in order to find the right solution for the maximum development of the child. Fourth, assist and represent the mother of the child in handling the cases currently being faced at the Syar'iyah Court. The challenges faced are: First, the lack of human resources at NGOs for Women and Children. Second, it is difficult to reconcile the father and mother of the child. Third, the whereabouts of the child and the father are unknown. Fourth, some mothers just gave up because they no longer fought for custody again.